Neutron Yield from (γ, n) and (γ, 2n) Reactions following 100 MeV Bremsstrahlung in a Tungsten Target - Khai, Nguyen Tuan; Thiep, Tran Duc; An, Truong Thi; Cuong, Phan Viet; Vinh, Nguyen The (Communications in Physics, 2009)
The photonuclear reactions of (γ, xn) or (γ, xnp) types can be used to produce high-intensity neutron sources for research and applied purposes. In this work a Monte-Carlo calculation has been used to evaluate the production yield of neutrons from the (γ, n) and (γ, 2n) reactions following the bremsstrahlung produced by a 100 MeV electron beam on a tungsten target